Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $\phi:R[x]\rightarrow C$ defined for a fixed $z\in C$ as $\phi(p(x))=p(z)$ where $p\in R[x]$. Then this map is supposed to be surjective. Could someone explain me please why?

share|improve this question
3  
What is $C$? And what is its relation to $R$? (is $R$ supposed to be a ring by the way) –  Nils Matthes Mar 6 '13 at 8:56
5  
Assuming that $R$ and $C$ are intended to be $\mathbb{R}$ and $\mathbb{C}$ respectively, then this is false. For example, let $z=0$; then the image of $\phi$ is just $\mathbb{R}$, not all of $\mathbb{C}$. –  Zev Chonoles Mar 6 '13 at 8:57
3  
Please give the full context. I suspect $C$ to be a simple extension of $R$ by $z$, all things being commutative. –  Andreas Caranti Mar 6 '13 at 9:13
    
Link to OP's prior variant where $R = C.\ \ $ –  Math Gems Mar 6 '13 at 18:24
add comment

2 Answers

I assume that $C$ wants to be $\Bbb C$ and $z\in\Bbb C\setminus\Bbb R$. (Else, if $z\in R$, then for all $p\in R[x]$, we have $p(z)\in R$ whatever ring $R$ is.)

Let's assume then that $z=a+bi$ for $a,b\in\Bbb R$ and $b\ne 0$. Then $$g(x):=\frac1b\cdot (x-a)$$ and for arbitrary $r+si\in\Bbb C$, consider $p(x):=r+s\cdot g(x)\ \in \Bbb R[x]$, then, as $g(z)=i$, we have $p(z)=r+s\cdot i$.

share|improve this answer
    
Note $\:z\in\Bbb C\setminus\Bbb R\:\Rightarrow\:\Bbb R[z] = \Bbb C\:$ follows immediately from $\rm\,[\Bbb C:\Bbb R] = 2\,$ is prime, see my answer. –  Math Gems Mar 6 '13 at 18:30
add comment

Let $\rm\,\bar R = \phi R,\,$ Then $\rm\, \phi\,$ onto $\rm\!\!\iff\!\! \phi(R[x]) = \bar R[z] = C.\:$ Thus $\,\phi\,$ is surjective iff $\rm\,C\,$ is the ring generated by adjoining $\,z\,$ to the subring $\rm\,\bar R\subseteq C.\,$ To say more requires knowing further details.

For example, if $\rm\,\phi : R\subset C\,$ are fields then $\,\phi\,$ is onto if $\rm\,[C:R] = p\,$ is prime, and $\rm\,z\not\in R,\:$ since then $\rm\,1 < [R[z]:R]\mid [C:R]=p,\,$ so $\rm\,[R[z]:R] = p.\,$ This is true, e.g. for $\rm\,R = \Bbb R,\ C = \Bbb C$.

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.